Impact of Entrepreneurship Training To Rural Farmers In Generation of Income, Growth And Maintenance of Poultry Farm In Namakkal District - P. Ranjithkumar and Dr. C. Gunasekaran (International journal of economic perspectives, 2022)
Agriculture and allied sector is the main stay of Indian economy. It creates employment opportunity for two-thirds of the population in the country. Among the various agriculture and allied activities, poultry farming is one of the important components of farmers’ for their income generation by providing eggs, meat, manures with an small investment. To achieve the desired results of poultry farmers, they are in need of adequate training to meet the challenges in poultry farm industry. The challenges are poultry immunity, health, demand and supply, farming technique, desire control, farm management practice are the important challenges for the poultry farmers. To manage these challenges, the poultry farmers are required an efficient training. In this context, the present study is examine the profile of the poultry farmers, reasons for selection of particular strain, the level of income and efficiency in poultry farm management before and after the training obtained by the poultry farmers. The present investigation was carried out in Nammakkal district of Tamilnadu in connection with an impact of entrepreneurship training to the rural farmers in generation of income, growth and maintenance of poultry farm. This study also exhibits the profile of poultry farmer, their awareness level, so on. In this study, one hundred and eighty four farmers who are practicing and non practicing poultry farmers were considered as the sample which is 25% of total farms in nammakkal district. The frequency, correlation and multiple regression analysis have been used for analyse the primary data. The suitable hypothesis has also been framed and analysed.